The e.ffect of simultaneous doping . of Pll in TJ..Q,6 htyer of 'T'lJ-xPb. Ba2Ca2Co_309- o s perconductors - -Jassim, K. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Tn   tÂ·  p.a,p r        We hae  reported it;vestigations O:U   theÂ·  effeot ofsimtHtaneous sÂ·ubs'tituti9n   of  :Pb . a;t tbe,1'1-based .IJPercqndl,lctor wasÂ·prepar.d by adcling; an .amounÂ· 0f Pb t. the TIJ-PbxBa;iCa2CuaOo'ti cor:npound. The: usu;d solid'7state  teactin  meJ;}Jo.d                                                             haS be:eu. applied t:mdr optimum  co_nditjon..Â· auJk po.lycrys.talline sari;lples.  hf!ve -beenp.reparQ by  the  tWo step .soli_d   tate  re.ctip:n  proeess;  It  has  bee 1• ohsewedthat the gj'own Il1-xPh.x.BaiGa2Cu30:6(with x =